2015
DOI: 10.1016/j.biortech.2015.08.096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of membrane orientation on fouling characteristics of forward osmosis membrane in concentration of microalgae culture

Abstract: Application of forward osmosis (FO) membrane to microalgae cultivation processes enables concentration of microalgae and nutrients with low energy consumption. To understand fouling characteristics of FO membrane in concentration of microalgae culture, we studied flux decline, flux recovery by cleaning, and foulants characteristics, in different membrane orientation of active-layer-facing-feed-solution (AL-FS) and active-layer-facing-draw-solution (AL-DS) modes. Batch concentration of Chlorella vulgaris was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…It can be seen from Fig. 1B respectively, which might be due to more serious membrane fouling and faster drop of water ux on AL-DS mode [22].…”
Section: Microbial Analysismentioning
confidence: 91%
“…It can be seen from Fig. 1B respectively, which might be due to more serious membrane fouling and faster drop of water ux on AL-DS mode [22].…”
Section: Microbial Analysismentioning
confidence: 91%
“…As the composition of solutes gets intricate, the interactions among the solute compounds or organisms aggravate the performance of a membrane. For example, the microbes in the feed and draw solutions produce byproducts such as polysaccharides and proteins [13]. Such byproducts get accumulated inside a membrane and result in a severer ICP.…”
Section: Internal Concentration Polarizationmentioning
confidence: 99%
“…While the PRO process has achieved appreciable technological advances in a number of research projects, nevertheless, several obstacles still hamper the commercialization of the process. For example, multiple types of research concluded that a stand-alone PRO process was not viable due to the inherent thermodynamic limits [9][10][11][12] and the vulnerability of a membrane to the fouling propensity [13][14][15][16][17][18][19]: the inherent thermodynamic limits and the vulnerability of a membrane to the fouling propensity will be elaborated in the upcoming sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPS are usually fractionated into three forms: soluble EPS or soluble microbial products (SMP); loosely bound-EPS (LB-EPS), which are present outer layer of EPS matrix; and tightly bound-EPS (TB-EPS) which are present in the inner layers of the EPS matrix [3]. Several review papers have highlighted roles of EPS in treatment performance of biological wastewater treatments such as conventional wastewater treatment, membrane bioreactor (MBR) [2], and forward osmosis membrane processes [4]. They have proved the fact that EPS considerably affect properties of activated sludge, directly determining charge, hydrophobicity/ hydrophilicity and adhesion ability of sludge surface [5].…”
Section: Introductionmentioning
confidence: 99%